Implanting Cobalt Atom Clusters within Nitrogen‐Doped Carbon Network as Highly Stable Cathode for Lithium–Sulfur Batteries - Zhang, Fenglong; Ji, Shan; Wang, Hui; Liang, Huagen; Wang, Xuyun; Wang, Rongfang (Small methods, 2021)
Realization of highly efficient sulfur electrochemistry, as well as the high capacity of lithium–sulfur (Li–S) batteries, can be achieved by the scientific construction of electrode host materials. In this study, using molten NaCl, a 3D porous nitrogen‐doped carbon with uniformly embedded Co atom clusters (Co/PNC) is developed by pyrolyzing the precursors with NaCl at high temperatures. In the composite structure, a network carbon skeleton containing hierarchical pores acts as an advanced matrix for sulfur electrodes, and the doping of N and Co is subject to inhibit the shuttle of long‐chain lithium polysulfides through chemical adsorption. The Co/PNC, with the optimized amount of Co, delivers an initial specific capacity of 1105.4 mAh g−1 at 0.2 C with a capacity drop of only 0.064% after the cell is charged and discharged for 300 cycles at 1 C, revealing its potential in promoting the large‐scale application of Li–S batteries. A 3D porous N‐doped carbon network with embedded Co atom clusters (Co/PNC) is developed by pyrolyzing in molten NaCl. In Co/PNC, network carbon skeleton containing hierarchical pores and the doping of N and Co is subject to inhibit the shuttle effect. The optimized Co/PNC delivers a capacity of 1105 mAh g−1 with high stability in the lithium‐sulfur cell.